A Novel Compact Microstrip Low-pass Filter with a Wide Rejection-Band and Sharp Roll-Off using Star-Shaped Resonator - Hayati, Mohsen; Faramarzi, Zahra; Amiri , Mozhgan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, a novel compact microstrip Low-Pass Filter (LPF) with a wide rejection-band and sharp roll-off using a starshaped resonator is presented. The proposed LPF provides some significant features, such as simple structure, low insertion-loss less than 0.1 dB from DC to 2.391 GHz in the pass-band and expanded stop-band with an attenuation level better than -20 dB from 2.842 GHz up to 20.65 GHz. The transition band is 0.27 GHz from 2.57 GHz to 2.84 GHz, with corresponding attenuation levels of -3 dB and -20 dB, respectively. The filter with a -3 dB cutoff frequency of 2.57 GHz has been designed, fabricated and tested, where the measurement results are in good agreement with the simulation results. The overall size of the proposed LPF is only 11.4 mm 13.6 mm.